Pengembangan Sistem Absensi Online dalam Memonitoring Kehadiran Mahasiswa untuk Mempermudah Proses Perkuliahan - Sahara, Siti; Syafiq, Muhammad Irsad; Suryadi, Faqih Dimas (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Technological developments are progressing rapidly nowadays. Especially developments in Information Technology science. This can be seen from everyday life, how Indonesian people in general always involve technology in carrying out daily activities. However, it is still rare for people to use technology to help with their work or fulfill work needs. It is not uncommon for attendance activities to become part of the assessment between lecturers and students, which influences the final grades received by students. And there is often fraud committed by students regarding attendance in order to meet the minimum attendance figures for teaching and learning activities. Taking absences between students is a common thing. This can be detrimental to lecturers, other students, and also students who carry out absentee activities. The attendance sheet used for student attendance is often damaged, even though later this attendance sheet will be used as a report regarding the teaching and learning activities carried out in one semester. If the document is damaged, it will affect the document checking process carried out by the university.